2021
DOI: 10.1016/j.bioactmat.2020.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid-engineered mesoporous polydopamine nanoparticles loaded with SPIO and Fe3+ as a novel theranostic agent for T1/T2 dual-mode MRI-guided combined chemo-photothermal treatment of hepatic cancer

Abstract: Hepatic cancer is a serious disease with high morbidity and mortality. Theranostic agents with effective diagnostic and therapeutic capability are highly needed for the treatment of hepatic cancer. Herein, we aimed to develop a novel mesoporous polydopamine (MPDA)-based theranostic agent for T1/T2 dual magnetic resonance imaging (MRI)-guided cancer chemo-photothermal therapy. Superparamagnetic iron oxide (SPIO)-loaded MPDA NPs (MPDA@SPIO) was firstly prepared, followed by modifying with a targeted molecule of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 60 publications
2
49
0
Order By: Relevance
“…[ 16 ] In general, PTT based on the single use of photothermal agents is quite limited due to the low treatment efficiency and side effects in avoiding malignant tumor metastasis and recurrence. [ 17 ] For effective cancer therapy, PTT has been combined with chemotherapy by integrating photothermal agents, such as gold nanostars, [ 18 ] molybdenum disulfide nanoflakes (MoS 2 ), [ 19 ] or conducting polymers [ 20 ] with chemotherapeutic drugs. [ 21 ] For instance, in a recent study, Zhang and co‐workers developed polydopamine (PDA)‐coated gold nanorods that can be loaded with cisplatin (Pt) through covalent coordination for effective combination of PTT and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] In general, PTT based on the single use of photothermal agents is quite limited due to the low treatment efficiency and side effects in avoiding malignant tumor metastasis and recurrence. [ 17 ] For effective cancer therapy, PTT has been combined with chemotherapy by integrating photothermal agents, such as gold nanostars, [ 18 ] molybdenum disulfide nanoflakes (MoS 2 ), [ 19 ] or conducting polymers [ 20 ] with chemotherapeutic drugs. [ 21 ] For instance, in a recent study, Zhang and co‐workers developed polydopamine (PDA)‐coated gold nanorods that can be loaded with cisplatin (Pt) through covalent coordination for effective combination of PTT and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Endoplasmic reticulum stress caused by calcium overload and excess ROS are considered to be two important pathological mechanisms of inflammatory response syndrome in ALI [11,29,30]. Melanin-like nanoenzymes are a series of macromolecules that contain phenolic hydroxyl and amino and imino acids in its structural units, which have been shown to have the functions of light protection [22], free radical capture [20], and photothermal conversion [31].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analysis demonstrated high necrotic rates as well as complete response rates in 37.5% of the cases. Affirming the potential of combined thermo-chemotherapy using doxorubicin and PDA-SPION, Shu et al observed greater in vitro cytotoxicity of such thermo-chemotherapy compared with either therapy alone [65]. In vivo experiments on a heterotopic HepG xenograft model as combined therapy likewise accounted for better treatment response, since combined therapy resulted in noteworthy tumor volume reduction, whereas exclusive chemo-or photothermal therapy solely attenuated tumor growth.…”
Section: Hepatocellular Carcinoma Hepatocellular Carcinoma: Mfhmentioning
confidence: 99%